Transcript of Media Roundtable for East Asia and the Pacific - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, remarked that the immediate priority for developing countries is widespread access to Coronavirus (COVID-19) vaccines that match their deployment programs. in response to the sharp increase in demand, the World Bank has increased financing for vaccines to twenty billion dollars globally over the next eighteen months. He spoke about providing grants to the countries that are most in need, including fragile and small states. The World Bank is working jointly with the IMF in order to use the Common Framework in order to provide debt relief for countries and create the fiscal space they need. The new World Bank climate change action plan is going to create a shift in paradigm in order to connect development and investment and to focus on priorities in terms of reducing greenhouse gas emissions.